Enriching nursing knowledge and practice in Jordanian government hospitals through basic life support simulation training: A randomized controlled trial - Abu-Wardeh, Yousef; W. Ahmad, Wan Muhamad Amir; Che Hamzah, Mohd Shaharudin Shah; Najjar, Yahya W.; Hassan, Intan Idiana (Belitung Raya Publisher - Belitung Raya Foundation, 2024)
Background: Healthcare providers must possess the necessary knowledge and skills to perform effective cardiopulmonary resuscitation (CPR). In the event of cardiopulmonary arrest, basic life support (BLS) is the initial step in the life-saving process before the advanced CPR team arrives. BLS simulation training using manikins has become an essential teaching methodology in nursing education, enhancing newly employed nurses’ knowledge and skills and empowering them to provide adequate resuscitation. Objective: This study aimed to evaluate the potential effect of BLS simulation training on knowledge and practice scores among newly employed nurses in Jordanian government hospitals. Methods: A total of 102 newly employed nurses were randomly assigned to two groups: the control group (n = 51) received standard training, and the experimental group (n = 51) received one full day of BLS simulation training. The training program used the American Heart Association (AHA)-BLS-2020 guidelines and integrated theoretical models such as Miller’s Pyramid and Kolb’s Cycle. Both groups were homogeneous in inclusion characteristics and pretest results. Knowledge and practice scores were assessed using 23 multiple-choice questions (MCQs). Data were analyzed using one-way repeated measures ANOVA. Results: The results indicated significant differences in knowledge scores, F(2, 182) = 58.514, p <0.001, and practice scores, F(2, 182) = 20.134, p <0.001, between the control and experimental groups at all measurement times: pretest, posttest 1, and posttest 2. Moreover, Cohen’s d reflected the effectiveness of BLS simulation training as an educational module, showing a large effect (Cohen’s d = 1.568) on participants’ knowledge levels and a medium effect (Cohen’s d = 0.749) on participants’ practice levels. Conclusion: The study concludes that BLS simulation training using the AHA-BLS-2020 guidelines and integrating theoretical models such as Miller’s Pyramid and Kolb’s Cycle significantly improves knowledge and practice scores among newly employed nurses, proving highly effective in enhancing their competencies in performing CPR. Implementing BLS simulation training in nursing education programs can significantly elevate the proficiency of newly employed nurses, ultimately improving patient outcomes during cardiopulmonary arrest situations. This training approach should be integrated into standard nursing curricula to ensure nurses are well-prepared for real-life emergencies. Trial Registry Number: NCT06001879